2018
DOI: 10.1111/medu.13519
|View full text |Cite
|
Sign up to set email alerts
|

A critical narrative review of transfer of basic science knowledge in health professions education

Abstract: Transfer of basic science knowledge to clinical reasoning is an essential component of HPE that requires further development for implementation and scholarship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 43 publications
2
37
0
3
Order By: Relevance
“…[10][11][12][13] In studying how expertise develops, researchers have found that trainees learning to make clinical diagnoses have better diagnostic skill retention and transfer when teaching involves integrating basic science and clinical knowledge. [14][15][16][17][18][19][20][21][22][23][24][25][26] Hence, identifying and selecting the relevant conceptual and procedural knowledge appears to be a key decision point when educators choose which content to teach.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In studying how expertise develops, researchers have found that trainees learning to make clinical diagnoses have better diagnostic skill retention and transfer when teaching involves integrating basic science and clinical knowledge. [14][15][16][17][18][19][20][21][22][23][24][25][26] Hence, identifying and selecting the relevant conceptual and procedural knowledge appears to be a key decision point when educators choose which content to teach.…”
Section: Introductionmentioning
confidence: 99%
“…In many ways, transfer may, therefore, be considered the cornerstone of all medical training. Yet, transfer as a psychological concept is rarely considered by medical educators and scientists, as suggested by Castillo et al . in this issue of the journal.…”
mentioning
confidence: 99%
“…However, only a handful of these studies (15 out of the 627 screened studies in Castillo et al. 's sample) have explored transfer from a conceptual and theoretical point of view. In other words, there is an abundance of publications that confirm that transfer can occur (evaluation), but few that explore when, why and how to optimise transfer from a theoretical and conceptual point of view (research).…”
mentioning
confidence: 99%
See 2 more Smart Citations